2014
DOI: 10.1089/aid.2013.0280
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Translocation and Cardiometabolic Risk Factors in HIV Infection

Abstract: The widespread access to antiretroviral treatment during the past decades has transformed HIV infection from a lethal disease to a chronic condition, in which the relative burden of non-AIDS-related chronic disorders such as cardiovascular disease, malignancy, renal, liver, and bone disease has increased. The adjusted relative risk for myocardial infarction is reported to be around 2-fold compared to that of the general population, which over time is likely to translate into increased absolute risk in an aging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 131 publications
(133 reference statements)
1
32
0
1
Order By: Relevance
“…All these mechanisms are incompletely understood and are the focus of active research. Other pathogens, such as cytomegalovirus, might also contribute to this T-cell activation [87].…”
Section: The Role Of Hiv Infection In Itself In the Pathogenesis Of Cmentioning
confidence: 99%
See 1 more Smart Citation
“…All these mechanisms are incompletely understood and are the focus of active research. Other pathogens, such as cytomegalovirus, might also contribute to this T-cell activation [87].…”
Section: The Role Of Hiv Infection In Itself In the Pathogenesis Of Cmentioning
confidence: 99%
“…Markers of microbial translocation correlate with markers of inflammation (such as hsCRP and IL-6), innate immune activation (such as sCD14 and sCD163), and coagulation (d-dimer) which are elevated in HIV-infected individuals and are predictive of morbidity (including CVD) and mortality [87][88][89][90][91][92].…”
Section: The Role Of Hiv Infection In Itself In the Pathogenesis Of Cmentioning
confidence: 99%
“…Some of the direct effects of HIV infection on cardiovascular integrity include microbial translocation1 and the effect of HIV protein Nef on ATP binding cassette transporter A1 (ABCA1),2 the mediator of cholesterol transport 3. Apart from the direct effects of HIV on cardiovascular integrity, some drugs for antiretroviral therapy (ART), mainly reverse transcriptase inhibitors (RTI) and protease inhibitors (PI), have been shown to cause metabolic changes such as dyslipidemia and insulin resistance 4–6.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that plasma RNA viremia [3], cell-associated HIV-DNA level [4] and microbial translocation [5] are potential causes to explain the chronic inflammation and immune activation associated with HIV infection [3,6,7]. In addition, microbial translocation is not only associated with immune activation but also with cardiovascular events [14,15], dyslipidemia [16], lipodystrophy [17] and ultimately would independently determine the rate of disease progression [18] and death [19]. In addition, microbial translocation is not only associated with immune activation but also with cardiovascular events [14,15], dyslipidemia [16], lipodystrophy [17] and ultimately would independently determine the rate of disease progression [18] and death [19].…”
Section: Introductionmentioning
confidence: 99%